Implant-supported maxillary incisor intrusion - Revathi Peddu; Kalyani Mallavarapu; Devikanth Lanka; Bhargavi Nuvusetty (Wolters Kluwer Medknow Publications, 2018)
Deep bite management and retention are cumbersome as the stability is questionable, especially when the correction is achieved by posterior extrusion in nongrowing patients. Hence, it is advisable to intrude the anteriors; however, as conventional methods of anterior intrusion tax the anchorage, choosing biomechanics which ensure stable anchorage is our goal. The use of mini-implants has revolutionized biomechanics in orthodontics with better results as far as anchorage is concerned. This case report supports the literature regarding the implant-supported anchorage for true intrusion.